Almond shell derived porous carbon for a high-performance anode of microbial fuel cells. Issue 12 (30th September 2019) - Li, Meizhen; Ci, Suqin; Ding, Yichun; Wen, Zhenhai
Abstract : The biomass of almond shells is used as a source for preparation of porous carbon that performs impressively as the anode of a microbial fuel cell. Abstract : The microbial fuel cell (MFC), as one of the most promising biotechnologies, has the capability to harvest electricity by electrochemically degrading organic matter in wastewater. In this study, we report a simple calcination carbonization process to prepare a set of carbon materials by using almond shells as a new type of biomass precursor. The as-prepared carbon is characterized as having a favorable structure and properties required for anode materials of a MFC with decent electrical conductivity. The MFC using the porous carbon obtained at 800 °C (PC-800) as the anode can generate a maximum power density of 4346 mW m −2, much higher than that of MFCs with carbon counterparts and commercial carbon cloth (CC) as the MFC anode.